Fertility Does not Quarantine: Coronavirus Disease 2019 Pandemic Impacts on in Vitro Fertilization Clinical Pregnancy Rates - Fernanda de Almeida Vieira; Ricardo Pasquini Neto; Mariana Cristina Gomes Morila; Jean Borges Curimbaba; Daniela Sasso Pasquini; Paulo Cesar Zimmermann Felchner; Gustavo Wandresen; Jan Pawel Andrade Pachnicki (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
Abstract Objective To understand the impact of the coronavirus disease 2019 pandemic on in vitro fertilization (IVF) clinical pregnancy rates and analyze factors that may have influenced their outcome. Methods This was a retrospective observational study conducted at a tertiary-care Brazilian fertility center. All fresh IVF and embryo warming cycles performed from March 11 to December 31, 2018-2021 were analyzed, and their data were used to calculate fertilization, embryo cleavage, cycle cancellation, embryo transfer (ET), and clinical pregnancy rates. Statistical tests were used to evaluate the alterations found. Logistic regression models were used to explore the association of the categorical variables with the observed clinical pregnancy rates. Data from 2018 and 2019 (prepandemic) and 2020 and 2021 (pandemic) were grouped. Results A total of 756 cycles were analyzed (n = 360 prepandemic and n = 396 pandemic). The age group of the patients, fertilization rates, and cleavage rates did not have significant differences (p > 0.05). There was a reduction in the percentage of fresh IVF and an increase in embryo warming cycles (p = 0.005) during the pandemic. There was also an increase in fresh cycle cancellations (p < 0.001) and a reduction in ET rates (p < 0.001). The pandemic had a negative impact on clinical pregnancy rates (p < 0.001) especially due to the increase in fresh cycle cancellations (p < 0.001). Conclusion Embryo warming cycles with subsequent frozen-thawed ET were presented as a viable alternative to continue assisted reproductive treatments against pandemic restrictions on fresh cycles, ensuring clinical pregnancy, albeit at a lower rate than that of the prepandemic period.